1990
DOI: 10.1007/bf00008195
|View full text |Cite
|
Sign up to set email alerts
|

Toxic cyanobacteria (blue-green algae) in Finnish fresh and coastal waters

Abstract: A survey of the occurrence of toxic blooms of cyanobacteria in Finnish fresh and coastal waters was made during 1985 and 1986. Toxicity of the freeze-dried water bloom samples was tested by mouse-bioassay (i.p.). Forty-four per cent (83/188) of the bloom samples were found to be lethally toxic. Hepatotoxic blooms (54) were almost twice as common as neurotoxic ones (29). Anabaena was the most frequently found genus in toxic and non-toxic blooms and it was present in all neurotoxic samples. Statistical associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(153 citation statements)
references
References 21 publications
(15 reference statements)
6
143
2
2
Order By: Relevance
“…The present study indicated that MC-LR and MC-RR were the primary microcystins within the cells in the reservoir of the Guanting, while only MC-LR was detected in water. In the present study, Microcystis was the main cyanobacteria in the Guanting Reservoir, which was in accordance with the results of regional studies in American and Finnish lakes [16,17]. [18].…”
Section: Contents and Species Of Microcystin In Water Samplessupporting
confidence: 92%
“…The present study indicated that MC-LR and MC-RR were the primary microcystins within the cells in the reservoir of the Guanting, while only MC-LR was detected in water. In the present study, Microcystis was the main cyanobacteria in the Guanting Reservoir, which was in accordance with the results of regional studies in American and Finnish lakes [16,17]. [18].…”
Section: Contents and Species Of Microcystin In Water Samplessupporting
confidence: 92%
“…The increasing eutrophication of fresh waters many of which include drinking water reservoirs by human activity has increased the occurrence and intensity of cyanobacterial blooms (Sivonen et al, 1990) and approximately 50% of them are known to be toxic (Codd, 1995). The most commonly occurring toxins produced by cyanobacteria are microcystins.…”
Section: Introductionmentioning
confidence: 99%
“…naegeliana was simultaneously detected with other toxic species, no conclusive considerations on its toxicity have been reported so far. Sivonen et al (1990) reported that the neurotoxicity of bloom samples collected from Finnish lakes was associated statistically with Anabaena (Dolichospermum) lemmermannii, Anabaena (Dolichospermum) flos-aquae and W. naegeliana. In other studies, various microcystins were found during blooms in which W. naegeliana was dominant (Willame et al, 2005;Baudin et al, 2006), and the presence of mcy genes in environmental samples characterized by the presence of this species was also reported (Oberholster et al, 2006).…”
Section: Discussionmentioning
confidence: 99%